2022
DOI: 10.1111/ijd.16528
|View full text |Cite
|
Sign up to set email alerts
|

Burden of atopic disease in Black and Hispanic patients with alopecia areata: a case–control study in the All of Us research program

Abstract: The first case of isolated facial cutanenous leishmaniasis in a Down syndrome infant: a case report and review of the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Although we demonstrated higher socioeconomic status (higher SDI) was associated with a higher risk of AA at the gross national level, possibly driven by an increased burden of metabolic and autoimmune disease, 51,52 the pattern could be different at subnational ethnic level. Although not thoroughly analysed in this GBD report, the prevalence of AA is known to be affected by ethnicity 53,54 . Previous studies have demonstrated a higher risk of AA in African Americans 54 and Asians 55 compared to Whites in the US and the United Kingdom, respectively.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…Although we demonstrated higher socioeconomic status (higher SDI) was associated with a higher risk of AA at the gross national level, possibly driven by an increased burden of metabolic and autoimmune disease, 51,52 the pattern could be different at subnational ethnic level. Although not thoroughly analysed in this GBD report, the prevalence of AA is known to be affected by ethnicity 53,54 . Previous studies have demonstrated a higher risk of AA in African Americans 54 and Asians 55 compared to Whites in the US and the United Kingdom, respectively.…”
Section: Discussionmentioning
confidence: 92%
“…Although not thoroughly analysed in this GBD report, the prevalence of AA is known to be affected by ethnicity. 53,54 Previous studies have demonstrated a higher risk of AA in African Americans 54 and Asians 55 compared to Whites in the US and the United Kingdom, respectively. A complex interplay between hereditary elements and environmental influences might contribute to disparities in AA risk across ethnic groups.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations